THE ESSENCE OF LANGUAGE IN UZBEK AND ENGLISH LITERARY DISCOURSE - Ismoilova Shaxnoza Ilxomovna (The Conference Hub, 2025)
This article delves into the fundamental essence of language as reflected in the literary discourse of Uzbek and English traditions. By analyzing metaphorical, semantic, and cultural dimensions, the study reveals how language serves not only as a tool for communication but also as a mirror of cultural identity and worldview. Drawing on scholarly research, including the comparative study of metaphors in both literary systems, this article explores structural, functional, and cognitive aspects that shape literary expression in Uzbek and English.
Keywords: literary discourse, metaphor, cultural identity, linguistic essence, comparative linguistics, holistic understanding.